Асоціативний портрет студентів України - Самійлик, Світлана (Lesya Ukrainka Eastern European National University, 2016)
The article describes an associative image of such a social group as students of Ukraine, particularly the students of higher educational institutions of different regions of the country: Zhytomyr Ivan Franko State University, Hryhoriy Skovoroda Pereyaslav-Khmelnytskyi State Pedagogical University, Kyiv National University of Trade and Economics, Lviv Polytechnic National University, Ivan Franko National University of Lviv, and Donetsk National University. The associations were collected during 2015 – 2016. For this purpose, one of the most popular methods in psycho- and cognitive linguistics, a free word association test, was used. У статті описано асоціативний портрет такої соціальної групи як студенти України, а саме студентів ВНЗ різних регіонів країни: Житомирського державного університету імені Івана Франка, ДВНЗ «Переяслав-Хмельницький ДПУ ім. Г. Сковороди», Київського національного торговельно-економічного університету, Національного університету «Львівська політехніка», Львівського національного університету імені Івана Франка, а також Донецького національного університету. Асоціації було зібрано протягом 2015–2016 років за допомогою одного з найпопулярніших методів у психо- та когнітивній лінгвістиці – методу вільного асоціативного експерименту.
Keywords: associative image; free word association test; stimulus; frequent reaction; асоціативний портрет; вільний асоціативний експеримент; стимул; частотна реакція